FINANCIAL RELATIONS OF ECONOMIC ENTITIES IN THE FINANCIAL MANAGEMENT SYSTEM OF THE REPUBLIC OF UZBEKISTAN - Toir Ruzimurodovich Kholmirzaev; Shomurod Yakubovich Yusupov (Web of Journals Publishing, 2024)
The article examines the financial relations of economic entities in the financial management system. A definition of financial relations, their essence and types is given. The main directions of managing financial relations within the framework of financial management are analyzed. Financial analysis is considered as a tool for managing financial relations.
Keywords: financial relations, financial management, planning of financial relations, organization of financial relations, control of financial relations, financial analysis.